A new and endangered species of Kingsleya Ortmann, 1897 (Crustacea: Decapoda: Brachyura: Pseudothelphusidae) from Ceará, northeastern Brazil - Pinheiro, Allysson P.; Santana, William (Zootaxa, 2016)
A new species of freshwater crab, Kingsleya attenboroughi n. sp., from the Arajara district, Ceará state, Brazil, is described and illustrated. The new species differs from congeners by having a short apical plate in the first gonopod, with anteriorly directed lobes and proximally angular; proximal lobe of the apical plate with conspicuous semicircular protuberance in mesial and sternal views; marginal process protruded, projecting mesially in sternal view and subquadrate in mesial view; and field of apical spines narrow, tapering distally, with small spines concentrated proximally. Opportunity is taken to illustrate K. gustavoi Magalhães, 2005, the closest allied species of K. attenboroughi n. sp. A key for the species of Kingsleya Ortmann, 1897 is provided.